Identification, expression profiles and antiviral activities of a type I IFN from gibel carp Carassius auratus gibelio. Issue 91 (August 2019) - Zhou, Yongze; Jiang, Nan; Fan, Yuding; Zhou, Yong; Xu, Chen; Liu, Wenzhi; Zeng, Lingbing
Abstract: Type I interferons, as a class of multipotent cytokines, play a key role in host antiviral immune responses. In this study, a type I IFN coding gene of gibel carp, Carassius auratus gibelio, Cag IFNa was cloned and sequenced. The full-length cDNA sequence of Cag IFNa consists of 724 nucleotides that encode a predicted protein of 183 amino acids. Cag IFNa has two highly conserved cysteine residues in the deduced protein, which is mostly conserved in the fish group I type I IFNs. Cag IFNa was identified as a member of the IFNa subgroup of group I type I IFNs by phylogenetic analysis. Cag IFNa transcripts were detected in all investigated tissues with higher levels in the liver, intestine, spleen and head kidney of gibel carp. Following injection with Cyprinid herpesvirus 2 (CyHV-2), Cag IFNa gene expression was significantly inhibited in the spleen but delayed and then increased in head kidneys. Similarly, while Cag IFNa expression was rapidly induced in gibel carp brain (GiCB) cells by poly I:C stimulation and its high induction level was delayed following CyHV-2 infection. Cag IFNa overexpression in GiCB cells drastically reduced virus CPE and titer. Furthermore, several genes associated with type I IFN signaling pathway including IRF3, IRF7, IRF9, STAT1, Mx1 and PKR were induced in GiCB cells overexpressing Cag IFNa upon CyHV-2 infection. These results show that Cag IFNa plays a role in antiviral immune system in gibel carp. Highlights: A type I IFN gene from gibel carp, Carassius auratus gibelio named Cag IFNa was cloned and characterized. The expression of Cag IFNa was investigated with CyHV-2 infection or poy I:C stimulation. The CyHV-2 propagation was remarkably inhibited in Cag IFNa over-expressed cells. The genes associated with type I IFN system were significantly induced by Cag IFNa.